Niveles De Sintomatología Depresiva Y Ansiosa En Los Adolescentes De La Institucion Educativa Teofilo Roberto Potes, Buenaventura 2023 (2023)
This research sought to describe the levels of depressive and anxious symptoms in adolescents from the Teófilo Roberto Potes Educational Institution, Buenaventura, from a quantitative, descriptive and cross-sectional methodology, for which a sample of 197 students was taken, who are in middle adolescence between 14 to 18 years. As instruments for the measurement of said symptomatology of Anxiety and depression in the participating adolescents, the BDI-II and the BAI, by Beck, were used.